Radical democratic pluralism : an alternative - Yüksel, Ayşe Seda. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2003., 2003)
This study will concentrate on the philosophical debate on pluralism in the last two decades, underlining in particular the radical democratic critique of liberalism through a perspective more sensitive to differences. The research question which guides the study is whether radical democracy can stand as a viable and consistent alternative to liberal pluralism. In order to do this, radical democratic pluralism is first compared with liberal pluralism and then with communitarian pluralism, which is the most significant critiques of liberal pluralism from within liberal theory. The study will distinguish between radical democracy as a critique and radical democracy as a project. It is argued that although radical democracy is correct in its diagnosis concerning the problems and deficits of liberal and communitarian pluralisms, it fails to offer concrete methods and strategies to solve these problems due to four main reasons which are grouped under two categories. The first category, which consists of theoretical shortcomings of radical democracy, examines the latter's exclusive focus on discourse as an all-explaining category and its formulation of a hierarchy of differences. The second category, on the other hand, deals with the lack of procedural and practical solutions in radical democratic project, and highlights the invisibility of the economic dimension and the lack of mechanisms to deal with antagonisms in practice.
Keywords: Cultural pluralism; Democracy.; Radicalism.